(untitled) (IITM JOURNAL OF BUSINESS STUDIES (JBS), 2021)
Mergers and Acquisitions have been the area of strategic focus for many corporate houses since the last two decades. It is now a global inorganic growth strategy to serve a variety of firm specific objectives like accessing new markets, foreign strategic assets, trade and supporting infrastructure and shareholder’s value creation. The pharmaceutical industry in India witnessed one of the biggest mergers in its history when Sun Pharma took over Ranbaxy Laboratories. The merger failed to create value for the shareholders of Sun Pharma and considerable amount of literature has corroborated the fact. The present study has attempted to gather statistical evidence to prove the fact of such failure to create value for the shareholders of Sun Pharma in an objective manner. Seven valuation ratios have been considered to measure the value creation by the merger. The results before and after the merger have been analysed for the purpose by way of an event study. The study has been based on secondary data collected for a ten-year window from the annual reports of both Sun Pharma and Ranbaxy laboratories as well as from Ace Equity © data product. This study has objectively proved that the acquiring firm was not able to create enough wealth for shareholders post acquisition.